PERSEPSI TAMU TENTANG PELAYANAN PRIMA KARYAWAN RECEPTION FORNT OFFICE DEPARTMENT DI HOTEL WHIZ PRIME PADANG - Nanda, Yudi Putra (RC-INSTITUT, 2019)
This research originated from the results of pre-research observations. The researchers found that the lack of excellent reception staff was evident from the presence of employees lacking in communication and lack of hospitality, lack of focus when guests were in crowded condition, lack of attention of reception staff to guests, and some employees reception who is not responsible for special guest requests that are not met. This study aims to describe the excellent service of the reception front office department staff at Padang Whiz Prime Hotel. This type of research is quantitative descriptive research. The sampling technique in this study was a non probability sampling of 30 guests. Data collection techniques are done by indirect communication by distributing questionnaires or questionnaires using a Likert scale that has been tested for validity and reliability, then the data is analyzed using the SPSS version 15.00 program. The results of the study concluded that overall the excellent service of the reception front office department employees in Padang Whiz Prime Hotel is in the good category with a percentage of 50% with an average of 89.43 in the range of 10.0 - <12.0 and Cronbach's Alpha at 0.967.